Prediction of temperate broadleaf tree species mortality in arid limestone habitats with stomatal safety margins. (17th May 2019) - Chen, Zhicheng; Li, Shan; Luan, Junwei; Zhang, Yongtao; Zhu, Shidan; Wan, Xianchong; Liu, Shirong
Abstract: A growing body of evidence highlights the occurrence of increased widespread tree mortality during climate change-associated severe droughts; however, in situ long-term drought experiments with multispecies communities for the prediction of tree mortality and exploration of related mechanisms are rather limited in natural environments. We conducted a 7-year afforestation trial with 20 drought-resistant broadleaf tree species in an arid limestone habitat in northern China, where the species displayed a broad range of survival rates. The stomatal and xylem hydraulic traits of all the species were measured. We found that species' stomatal closure points were strongly related to their xylem embolism resistance and xylem minimum water potential but not to their survival rates. Hydraulic failure of the vascular system appeared to be the main cause of tree mortality, and the stomatal safety margin was a better predictor of tree mortality than the traditionally considered xylem embolism resistance and hydraulic safety margin. We recommend the stomatal safety margin as the indicator for predicting drought-induced tree mortality and for selecting tree species in future forest restorations in arid regions.